First-Generation autologous chondrocyte implantation in patients with cartilage defects of the knee: 7 to 14 years' clinical and magnetic resonance imaging follow-up evaluation - Moradi, Babak; Schönit, Eva; Nierhoff, Corinna; Hagmann, Sébastien; Oberle, Doris Franziska; Gotterbarm, Tobias; Schmitt, Holger; Zeifang, Felix (Arthroscopy, 2012)
Purpose: The purpose of this study was to evaluate the overall long-term improvement of autologous chondrocyte implantation (ACI) treatment in terms of patient satisfaction, clinical assessment, and magnetic resonance imaging (MRI) evaluation. Furthermore, we aimed to assess the impact of independent variables on clinical outcomes and patient satisfaction. Methods: We evaluated 23 patients (mean age, 30.5 ± 8.2 years) with full-thickness chondral lesions of the distal femur who underwent first-generation ACI with periosteum between 1997 and 2004. The Lysholm score, Tegner activity score, subjective International Knee Documentation Committee score, numeric rating scale score, and Short Form 36 score were used for clinical assessment preoperatively, at 1 year postoperatively, and at 7 to 14 years (mean, 9.9 years) after surgery. MRI was performed to evaluate the cartilage preoperatively and at final follow-up, by use of the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score. Results: ACI resulted in a substantial improvement in all clinical outcome parameters, even as much as 14 years after implantation, although a small deterioration was noticed between intermediate and final evaluations in some outcome parameters. Of the patients, 73.1% stated that they would undergo the operation again. Younger patients with a shorter duration of preoperative symptoms and smaller defect sizes benefited most. MRI findings confirmed complete defect filling in 52.3% of the patients at final follow-up. Conclusions: Our long-term results confirm that first-generation ACI is an effective treatment for large full-thickness chondral and osteochondral lesions of the knee joint. Younger patients with a shorter duration of preoperative symptoms and smaller defect size benefited most in our study.Level of Evidence Level IV, therapeutic case series.